2022
DOI: 10.1590/0103-8478cr20210446
|View full text |Cite
|
Sign up to set email alerts
|

Different calcium sources on the productive performance and bone quality of meat quail

Abstract: This study was developed to examine the effect of using charru mussel-, maçunim- and oyster-shell meals as calcium sources on the productive performance, carcass yield and bone parameters of meat quail. A total of 250 one-day-old non-sexed European quail were used. The birds were distributed into five treatments (calcium sources: calcitic lime, calcium carbonate, charru mussel shell meal, maçunim shell meal or oyster shell meal) in a completely randomized design with five replicates and ten birds per experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
0
0
Order By: Relevance
“…Similarly, Mendonca et al (2022) conducted an investigation that explored different organic calcium sources, including calcitic lime, calcium carbonate, charru mussel shell meal, macunim shell meal, and oyster shell meal. The study revealed that these sources had no impact on the overall weight at slaughter, as well as the absolute and relative weights of the bird's carcass, cuts, and edible offal.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Similarly, Mendonca et al (2022) conducted an investigation that explored different organic calcium sources, including calcitic lime, calcium carbonate, charru mussel shell meal, macunim shell meal, and oyster shell meal. The study revealed that these sources had no impact on the overall weight at slaughter, as well as the absolute and relative weights of the bird's carcass, cuts, and edible offal.…”
Section: Carcass Traitsmentioning
confidence: 99%
“…Heads, skin, trimmings, fins, scales, entrails, and bones of fish [64] Animal feed, biodiesel/biogas, diet foods (chitosan), food packaging (chitosan), cosmetics (collagen), and soil fertilizers [64] Crustacean shells [64] Animal feed, fertilizers, and for the removal of organic compounds from anionic metal compounds and heavy metal ions [65] By-products of crab production [64] Fish meal substitute [66] Charru mussel, maçunim and oyster shell meals [67] Source of calcium in the diet of European quails [67] Processed chicken feathers (autoclaved with 0.5% NaOH) The component in 2 mm granular granules intended for feeding fish [68] Chicken fat Feedstock for biodiesel production [69] Bird meal Biochar and bio-oil for use as heating and transport fuel [70] Poultry slaughter waste A ruminant feed with huge potential as cleaner animal feed for pollution prevention [71]; conversion to biogas by anaerobic digestion [72] Bird droppings Biochar and bio-oil for use as heating and transport fuel [70]. Raw material for fertilizer [73] Broiler litter Feed for male deer [74] Bones of farm animals, bone food residues Feed elements for creating diets for feeding pigs [75], glue [76] Blood of farm animals Feed blood meal [77] Remains of bird feathers Hydrolyzed feather meal [HFM] [77], bio-based glue [78] Keratin waste from chickens, ducks, geese, turkeys (feathers, hair), goats, and sheep (wool, hooves, horns, nails) Animal feed, fertilizers [79] Egg shells, classified as waste by the food industry [79,80] In the production of compound feed, in fish farming and feed for target animals, in the production of biochar [81], raw materials for growing Lingzhi mushrooms (Ganoderma lucidum) [82] The fishing industry is central to the economy for several countries in the world.…”
Section: Type Of Animal Waste Purpose Of Animal Wastementioning
confidence: 99%
“…Quail farming has grown in recent years and stands out in the poultry sector owing to the current technical production and the new forms of marketing eggs (MENDONÇA et al, 2022). Different recommendations exist regarding the formulation of diets for Japanese quail: either using one single diet throughout the rearing period; or two diets, one for the starter and another for the grower phase (SILVA & COSTA, 2009;ROSTAGNO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%